Expression of pituitary tumor-transforming 2 in human glioblastoma cell lines and its role in glioblastoma tumorigenesis - GUO, YUNBAO (Exp Ther Med, 2016)
The present study aimed to investigate the association between the expression of pituitary tumor-transforming 2 (PTTG2), and cell proliferation, invasion and apoptosis in glioblastoma. The U251 human glioblastoma cell line was transfected with the pcDNA-PTTG2 and small interfering (si)RNA-PTTG2 plasmids using Lipofectamine 2000. The expression of PTTG2 in U251 glioblastoma cells was determined using reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blot analysis. The association between PTTG2 expression, and cell proliferation, invasion and apoptosis in vitro were investigated using an MTT assay, Matrigel Transwell assay and flow cytometry combined with Annexin V/propidium iodide staining, respectively. RT-qPCR and western blot analysis demonstrated that PTTG2 mRNA and protein expression were significantly overexpressed and significantly suppressed following transfection with pcDNA-PTTG2 and short interfering RNA (siRNA)-PTTG2 plasmids, respectively (P<0.05). In addition, the cell proliferation rate and invasive cell number in cells with overexpressed PTTG2 were significantly higher compared with cells in the untreated group, and the invasive cell number in the siRNA-PTTG2 group was significantly lower than the untreated group (P<0.05). Flow cytometry analysis demonstrated that, compared with the untreated group, the quantity of apoptotic cells in PTTG2 overexpression group was significantly reduced, and the quantity of apoptotic cells in the siRNA-PTTG2 group was increased. Similar results were obtained with regards to the expression level of caspase-3. The results of the present study indicate that PTTG2 overexpression promotes cell proliferation and invasion during glioblastoma progression. In addition, the results suggest that PTTG2 overexpression inhibits cell apoptosis in glioblastoma by affecting caspase-3-dependent signaling pathways. It can therefore be suggested that PTTG2 may serve as a novel therapeutic target for treating glioblastoma.